Evaluation of Cervical Proprioception and its Association with Disability in Neck Pain: A Cross Sectional Study - Khan, Hafiz Yaseen; Adnan, Muhammad; Basit, Syed Abdul; Khan, Sudair; SGul, Saba; Irzam Haroon, Irzam Haroon; Gull, Neelo; Khan, Noman (Indus Journal of Bioscience Research, 2025)
Aims: The aim of this study to evaluate cervical proprioception and its relationship with disability in neck pain. Methods: This was cross sectional study to explore association between cervical proprioception and disability in neck pain. 91 patients were examined for cervical proprioception by laser tracking method or JPE for flexion, extension, right rotation and left rotation. Neck disability index questionnaire was filled by patients for checking disability and laser tracker was used for proprioception. Results: Most of the participants 52.7% had mild disability. Patients were from age 18-65 years having mean age 37.8± 10.7, the mean score of neck disability index was 14.9±8.0, the chi square test showed no association for flexion, extension and right rotation with proprioception as their P- values are 0.299>0.05, 0.442>0.05, 0.694>0.05 and left rotation showed significant association between left rotation and proprioception. Most of the participants 80.2% had forward head posture. Majority 47.7% were in age between 20-30 and having mean age 33.8±8.8. The mean score of neck disability index was 5.88±4.9. The chi square test showed no significant association (P>0.05) between forward head posture and neck pain. Conclusion: This study concluded that cervical proprioception has no significant association with disability in neck pain.